Pengaruh Metode Bernyanyi pada Perkembangan Kognitif Anak Usia 4-5 Tahun - Puspitasari, Dani; Gea, Grace Arta Wijayanti; Hura, Mersisanti; Limu, Neci Larichi Hudi; Telaumbanua, Veronica Aprilian; Setia, Yulia (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2024)
Singing is one of the methods used by teachers in the classroom. It is a familiar activity for children because it is very fun and builds enthusiasm. It is very good for stimulating the cognitive development of young children who are in the golden phase. This study aims to see the effect of singing methods on the cognitive development of children aged 4-5 years who are in the pre-operational stage. Study was conducted at a kindegartedn in Surabaya. Qualitative approach was used to collect and analyze data. Researchers used modified songs in this study. The songs included material at each meeting and was sung together with the children in the class. The results of the analysis show that song is an effective medium for improving the cognitive abilities of children aged 4-5 years with the highest test results reaching an average score of 97.5. interviews also generate some important implication for early childhood educators.